The Social Work Role in Reducing 30-Day Readmissions: The Effectiveness of the Bridge Model of Transitional Care. Issue 3 (2nd April 2016) - Alvarez, Renae; Ginsburg, Jacob; Grabowski, Jessica; Post, Sharon; Rosenberg, Walter
ABSTRACT: The hospital experience is taxing and confusing for patients and their families, particularly those with limited economic and social resources. This complexity often leads to disengagement, poor adherence to the plan of care, and high readmission rates. Novel approaches to addressing the complexities of transitional care are emerging as possible solutions. The Bridge Model is a person-centered, social work-led, interdisciplinary transitional care intervention that helps older adults safely transition from the hospital back to their homes and communities. The Bridge Model combines 3 key components—care coordination, case management, and patient engagement—which provide a seamless transition during this stressful time and improve the overall quality of transitional care for older adults, including reducing hospital readmissions. The post Affordable Care Act (ACA) and managed care environment's emphasis on value and quality support further development and expansion of transitional care strategies, such as the Bridge Model, which offer promising avenues to fulfil the triple aim by improving the quality of individual patient care while also impacting population health and controlling per capita costs.